Stage collapse at the Indiana State Fair - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
The case concerns the dire weather conditions that caused problems to August's 2011 State Fair in Indiana during a concert. The Fair Commission was fined US$6,300 for failing to take into account the severe weather conditions and their potential impact on the safety of the concert fans.